Untargeted metabolomics identifies succinate as a biomarker and therapeutic target in aortic aneurysm and dissection. (17th September 2021) - Cui, Hongtu; Chen, Yanghui; Li, Ke; Zhan, Rui; Zhao, Mingming; Xu, Yangkai; Lin, Zhiyong; Fu, Yi; He, Qihua; Tang, Paul C; Lei, Ienglam; Zhang, Jifeng; et al.
Abstract: Aims: Aortic aneurysm and dissection (AAD) are high-risk cardiovascular diseases with no effective cure. Macrophages play an important role in the development of AAD. As succinate triggers inflammatory changes in macrophages, we investigated the significance of succinate in the pathogenesis of AAD and its clinical relevance. Methods and results: We used untargeted metabolomics and mass spectrometry to determine plasma succinate concentrations in 40 and 1665 individuals of the discovery and validation cohorts, respectively. Three different murine AAD models were used to determine the role of succinate in AAD development. We further examined the role of oxoglutarate dehydrogenase (OGDH) and its transcription factor cyclic adenosine monophosphate-responsive element-binding protein 1 (CREB) in the context of macrophage-mediated inflammation and established p38α MKO Apoe –/– mice. Succinate was the most upregulated metabolite in the discovery cohort; this was confirmed in the validation cohort. Plasma succinate concentrations were higher in patients with AAD compared with those in healthy controls, patients with acute myocardial infarction (AMI), and patients with pulmonary embolism (PE). Moreover, succinate administration aggravated angiotensin II-induced AAD and vascular inflammation in mice. In contrast, knockdown of OGDH reduced the expression of inflammatory factors in macrophages. The conditional deletion of p38α decreased CREB phosphorylation, OGDH expression, and succinate concentrations. Conditional deletion of p38α in macrophages reduced angiotensin II-induced AAD. Conclusion: Plasma succinate concentrations allow to distinguish patients with AAD from both healthy controls and patients with AMI or PE. Succinate concentrations are regulated by the p38α–CREB–OGDH axis in macrophages. Graphical Abstract: